Problems of B.Ed. Teacher Trainees: A Survey - Rathod , Rajesh R. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2016)
In the present study Researcher tried to identify the problems of B.Ed. Teacher trainees. Random sampling technique was used for selecting the sample. The total sample was that of 90 B.Ed. Teacher trainees from three B.Ed. colleges. Researcher used Survey method in this study. The collected data were analyzed by using the qualitative research methods. Results shows that Lack of fluency in the language of instruction, Lack of ICT related subject in curriculum, In-Ability to create and sustain an effective learning environment, students feel stage fear after the experience of forty stray lessons and New teaching techniques were not used in instructional process. Separate rooms were not provided for every method. Transport facility was not provided to students by the management. Some college don’t have LCD projector. Lack of expert teachers. Lack of Proper guidance for preparing qualitative lesson plan. Lesson Planning format were no change. Lack of subject wise teaching aids in every college and various useful equipments in Psycho lab for teaching psychology. Most of the colleges don’t have sufficient numbers of teaching aids and reference books in the library. Sometimes librarians’ behavior is problematic for students. Lack of arrangement of the Campus interview by College and Expert lectures for the development of Student.